Cara Mengatasi Masalah Pada Siswa SMP Yang Terindikasi Peer Problem - Widiantari, Yuniar, Usmi Karyani, S.Psi, M.Si, Psi (2017)
peer problem is the big problem which has big impact to the developmental of adoloscents for the next time. Peer problem can be a stressor and pressure, when experiencing stress and pressure people will try to reduce the source of pressure. A survey from 141 showed from 141 student of junior high school about 21% had differences with their peer group and 81% said that they got conflicts with their peer in their school. The purpose of this study was to know the dynamic of coping who had peer problem indication. The researcher used qualitative narrative descriptive approach. The method of this study was semi structure interview with 5 informans where is 2 male and 3 female who indicates peer problem with high level or high need (HN) which knowing from Strenghts and Difficulties Questionaire scale (SDQ). The results of this study showed the problem of junior high school student who had peer problem indication were disturbed by the other friends, unlike by other friends, and difficult to find a friends. The part who included junior high school student to appear peer problem was school friend and playmate. The part who helped junior high school student to solve the problem was friend, parents, brother and teacher. The startegi coping are 54,9% used adaptive problem focused coping, where is have positive primary appraisal, then scondary appraisal able to solve the problem. 12,9% used maladaptive problem focused coping, where is have negative primary appraisal, then scondary appraisal unable to solve the problem. 29,0% used maladaptive emotion focused coping, where is have negative primary appraisal, then scondary appraisal unable to solve the problem. 3,2% used adaptive emotion focused coping, where is have positive primary appraisal, then scondary appraisal able to solve the problem. Keyword : junior high school, peer problem, coping